The experiences of children and young people with special educational needs and disabilities during the COVID-19 pandemic: a reflexive thematic analysis - Gibson, Hannah (2022)
COVID-19 (SARS-CoV-2) was declared to be a pandemic and health emergency by the World Health Organisation (WHO) in March 2020. It led to a series of worldwide ‘lockdowns’ where people were instructed to stay at home. Many children and young people (CYP) did not attend school during this time and COVID-19 has been described as an unprecedented disruption to education in the UK (The Nuffield Foundation, 2020). It is thought that CYP are likely to experience the impacts and consequences of the COVID-19 pandemic for many years to come (Thompson et al, 2021) and there is deepening concern about the shorter and longer-term impacts for those already identified as vulnerable, such as CYP with special educational needs and disabilities (SEND) (McCluskey et al, 2021). Every CYP has the right to express their views regarding all matters that affect them (UN General Assembly,1989), however, as the world has responded to COVID-19 and extensive research is carried out, there is a notable lack of studies hearing directly from CYP about their experiences of COVID-19. To be able to understand a particular phenomenon within a vulnerable population, the perspectives of those with direct experience need to be listened to and understood (Prunty et al, 2012). The current research therefore asked the question: how are CYP with SEND experiencing the COVID-19 pandemic? It aimed to listen to, interpret and report the experiences of CYP with SEND during COVID-19. A qualitative methodology was utilised, and six semi-structured interviews carried out with secondary school aged participants, all with SEND. The data gathered was analysed and interpreted using Reflexive Thematic Analysis (TA) and findings presented according to this approach. The findings illustrated four main themes: government restrictions, learning in a pandemic, relationships and the ‘new normal’. These are presented and discussed in light of theory, research and literature. Methodological considerations are addressed, particularly regarding the data collection process and the sample limitations. Findings are discussed in relation to the research goal which was to provide information and develop understanding for educational services, settings and communities about how best to support CYP with SEND during and following the COVID-19 pandemic. The potential implications for education settings, Educational Psychologists (EP), Local Authorities (LA) and the wider government are acknowledged. The findings also illuminate a number of suggestions for future research.